The chronicles of Zurara: royal court, aristocracy and chivalry in fifteenth-century Portugal - Aguiar, Miguel (2018)
This article aims to analyse Gomes Eanes de Zurara’s chronicles, considering not only form and style, but also the message regarding the general purposes of the text. Chronicles were seen as “nobles' mirrors” based on chivalric principles, which functioned as a way of shaping aristocracy’s behaviour, while simultaneously defining the competitivity amid that social group. Nonetheless, these texts can also be analysed as pieces of ‘propaganda’ on behalf of the crusade in North Africa, validating and reinforcing internally and externally the zeal and eagerness of this same movement.   Bibliography Printed sources ÁLVARES, Frei João – Trautado da Vida e Feitos do muito Vertuoso S.or Ifante D. Fernando. Ed. Adelino de Almeida Calado. Coimbra: Universidade de Coimbra, 1960, vol. I. DOCUMENTOS DO ARQUIVO HISTÓRICO da Câmara Municipal de Lisboa – Livros de Reis. Lisboa: Câmara Municipal de Lisboa, 1959, vol. 3. DOM DUARTE – Leal Conselheiro. Ed. Maria Helena Lopes de Castro. Lisboa: Imprensa Nacional – Casa da Moeda, 1998. DOM DUARTE – Livro da Ensinança de Bem Cavalgar Toda a Sela que fez El-Rey Dom Eduarte. Ed. Joseph M. Piel. Lisboa: Imprensa Nacional Casa da Moeda, 1986. DOM DUARTE – Livro dos Conselhos de El-rei D. Duarte (Livro da Cartuxa). Ed. João José Alves Dias e A. H. de Oliveira Marques. Lisboa: Estampa, 1982. Leonor de Portugal, Imperatriz da Alemanha: diário de viagem do Embaixador Nicolau Lanckman de Valckenstein. Ed. Aires de Nascimento. Lisboa: Cosmos, 1992. MONUMENTA HENRICINA. Ed. António J. Dias Dinis. Coimbra: Comissão Executiva das Comemorações do V Centenário da Morte do Infante D. Henrique, 13 vols. ORDENAÇÕES AFONSINAS. Lisboa: Fundação Calouste Gulbenkian, 1998, Livro I. ZURARA, Gomes Eanes de – Crónica da Tomada de Ceuta por el rei D. João I. Ed. Francisco Maria Esteves Pereira. Lisboa: Academia das Ciências de Lisboa, 1915. – Crónica do Conde D. Duarte de Meneses. Ed. Larry King. Lisboa: Faculdade de Ciências Sociais e Humanas – Universidade Nova de Lisboa, 1978. – Crónica dos feitos notáveis que se passaram na conquista de Guiné por mandado do infante D. Henrique. Ed. Torquato de Sousa Soares. Lisboa: Academia Portuguesa da História, 1997, 2 vols.   Studies AGUIAR, Miguel – Ideologia Cavaleiresca em Portugal no Século XV. Porto: Universidade do Porto, 2016. Dissertação de Mestrado. BERTOLI, André – O Cronista e o Cruzado: a revivescência do Ideal Cavaleiresco no Outono da Idade Média Portuguesa (Século XV). Curitiba: Universidade de Curitiba, 2009. Dissertação de Mestrado. – “Modelos de ação bélica na Crônica de D. Duarte de Meneses - Texto, Contexto e Representação”. Mirabilia 15 (2012/2), pp. 171-201. BUESCU, Ana Isabel – “Um Discurso sobre o Príncipe: a “pedagogia especular” em Portugal no século XVI”. Penélope 17 (1997), pp. 33-50. BRAGANÇA, José de – “Introdução”. In ZURARA, Gomes Eanes de – Crónica da Guiné. Porto: Livraria Civilização, 1937, vol. I, pp. I-XLV. CAMPOS, Nuno Silva – D. Pedro de Meneses e a construção da casa de Vila Real (1415-1437). Lisboa: Colibri/CIDEHUS, 2004. COELHO, Maria Helena da Cruz – “Aristocracia Vilã”. in COELHO, Maria Helena da Cruz e HOMEM, Armando Luís de Carvalho (coord.) – Portugal em Definição de Fronteiras. Lisboa: Presença, 19, pp. 253-260. CURTO, Diogo Ramada – “A Literatura e o Império: entre o espírito cavaleiresco, as trocas da corte e o humanismo cívico”. in BETHENCOURT, Francisco e CHAUDHURI, Kirti (dir.) – História da Expansão Portuguesa. Lisboa, Círculo de Leitores, 1998, vol. I, pp. 434-454. DINIS, A. J. Dias – Vida e Obras de Gomes Eanes de Zurara. Lisboa: Agência Geral das Colónias, 1949, vol. I. DUARTE, Luís Miguel – “Os melhores da terra (um questionário para o caso português)”. in BARATA, Filipe Themudo (ed.) – Elites e redes clientelares na Idade Média: problemas metodológicos. Lisboa: Colibri e CIDEHUS-EU, 2001, pp. 91-106. – Ceuta, 1415: Seiscentos anos depois. Lisboa: Livros Horizonte, 2015. FERNANDES, Adriano – A Crónica do Conde D. Duarte de Meneses de Gomes Eanes de Zurara: estudo histórico-cultural e edição semidiplomática. Vila Real: Universidade de Trás-os-Montes e Alto Douro, 2007, 2 vols. Tese de Doutoramento. FIGUEIREDO, Albano – O ideal de cavalaria na crónica da Tomada de Ceuta de Gomes Eanes de Zurara. Coimbra: Universidade de Coimbra, 1996. Dissertação de Mestrado. – “O narrador e o herói na Crónica da Tomada de Ceuta de Gomes Eanes de Zurara”. in Figura: Actas do II Colóquio da Secção Portuguesa da Associação Hispânica de Literatura Medieval. Faro: Faculdade de Ciências Humanas e Sociais da Universidade do Algarve, 2001, pp. 89-109. – A Crónica Medieval Portuguesa: génese e evolução de um género (sécs. XIV-XV). A dimensão estética e a expressividade literária. Coimbra: Universidade de Coimbra, 2005. Tese de Doutoramento. – “Viagem, cavalaria e conquista na Crónica de Guiné de Gomes Eanes de Zurara”. in Modelo: Actas do V Colóquio da Secção Portuguesa da Associação Hispânica de Literatura Medieval. Porto: Departamento de Estudos Portugueses e de Estudos Românicos – Faculdade de Letras da Universidade do Porto, 2005, pp. 25-33. FONSECA, Luís Adão. “Uma carta do Condestável Dom Pedro sobre a política marroquina de D. Afonso V”. Revista da Faculdade de Letras: História 1ª Série, vol. I (1970), pp. 83-96. GAUCHER, Elisabeth – La Biographie Chevaleresque: typologie d'un genre (XIII-XV siècle). Paris: Honoré-Champion Éditeur, 1994. GIBELLO BRAVO, Víctor – La Imagen de la Nobleza Castellana en la Baja Edad Media. Cáceres: Universidad de Extremadura, 1995. GOMES, Rita Costa – A Corte dos Reis de Portugal. Lisboa: Difel, 1995. – “Zurara and the Empire: Reconsidering Fifteenth-century Portuguese Historiography”. Storia della storiografia 47 (2005), pp. 56-89. KAEUPER, Richard W. – Chivalry and Violence in Medieval Europe. Oxford: Oxford University Press, 1999. KING, Larry – “Introdução”, in ZURARA, Gomes Eanes de – Crónica do Conde D. Duarte de Meneses. Ed. Larry King. Lisboa: Faculdade de Ciências Sociais e Humanas – Universidade Nova de Lisboa, 1978, pp. 21-40. LEITE, Duarte – Acerca da “Cronica dos Feitos de Guinee”. Lisboa: Bertrand, 1941. MONTEIRO, João Gouveia – “A Cultura Militar da Nobreza na primeira metade de Quatrocentos”. Revista de História das Ideias 19 (1997), pp. 195-229. MONTEIRO, Nuno Gonçalo – O Crepúsculo dos Grandes: a Casa e o Património da Aristocracia em Portugal (1750-1832). Lisboa: Imprensa Nacional Casa da Moeda, 2003. MORSEL, Joseph – L’aristocratie médiévale. Paris: Armand Colin, 2004. PIMPÃO, Álvaro Júlio da Costa – A “Crónica dos feitos de Guinee”: as minhas “teses” e as “teses” de Duarte Leite. Coimbra: Livraria Gonçalves, 1941. – Escritos Diversos. Coimbra: Universidade de Coimbra, 1972. PONTES, Luís Filipe – Do mundo da corte ao mundo da memória. Subsídios para o estudo da mentalidade cavaleiresca da nobreza portuguesa, 1400-1521. Lisboa: Universidade Nova de Lisboa, 2008. Dissertação de Mestrado. RODRÍGUEZ VELASCO, Jesús – El Debate sobre la Caballería en el siglo XV: la Tratadística Caballeresca Castellana en su marco Europeo. Salamanca: Junta de Castilla y León, 1996. ROSA, Maria de Lurdes – O Morgadio em Portugal: Sécs. XIV-XV. Lisboa: Estampa, 1995 – “Mortos – “tidos por vivos”: o Tribunal Régio e a capacidade sucessória das “Almas em Glória” (Campanhas Norte- Africanas, 1472-c. 1542)”. Anais de História de Além-Mar 6 (2005), pp. 9-46. – “Velhos, novos e mutáveis sagrados…um olhar antropológico sobre as formas “religiosas” de percepção e interpretação da conquista africana (1415-1521)”. Lusitânia Sacra 18 (2006), pp. 13-85. RUSSELL, Peter – Henrique, o Navegador. Lisboa: Horizonte, 2004. SARAIVA, António José – História da Cultura em Portugal. Lisboa: Jornal do Fôro. 1950, 2 vols. – O Crepúsculo da Idade Média em Portugal. Lisboa: Gradiva, 1998. SERRÃO, Joaquim Veríssimo – Cronistas do Século XV posteriores a Fernão Lopes. Lisboa: Instituto de Cultura e Língua Portuguesas, 1989. SOUSA, Bernardo Vasconcelos e – “Linhagem e Identidade Social na Nobreza Medieval Portuguesa (Séculos XIII-XIV) ”. Hispania vol. LXVII, nº 227, pp. 881-898. TAYLOR, Craig – “English Writings on Chivalry and Warfare during the Hundred Years War”. in CROSS, Peter e TYERMAN, Christopher (dir.) – Soldiers, Nobles and Gentlemen: Essays in Honour of Maurice Keen. Woodbridge: Boydell, 2009, pp. 64-84. – “Military Courage and Fear in the Late Medieval French Chivalric Imagination”. Cahiers de Recherches Médiévales et Humanistes 24 (2012), pp. 129-147. – Chivalry and the Ideals of Knighthood in France during the Hundred Years War. Cambridge: Cambridge University Press, 2013.